Prenosljivost in časovna omejenost nepravih stvarnih služnosti in služnosti v javno korist - Plavšak, Nina (Podjetje in delo, 2016)
The relatively tight regulation of quasi in rem easements and easements in the public interest in the practice causes problems with (correct, reasonable) application of certain general rules the Law of Property Code. In the article, authors analyze all aspects of (non)transferability and temporal limitation of these types of easements. Both types of easements have in common that they are non-transferable in the meaning that their beneficiary (the holder of easement) cannot effectively transfer this easement to a new beneficiary. Since both types of easements are established for the benefit of a particular person, they are bound to that person or in the case of a legal person to carrying out the undertaking of that legal person. Therefore, they only cease if the legal person (the beneficiary) ceases without legal succession. An easement in the public interest has an additional feature of being tied to the right to manage the performance of public infrastructure. Therefore, the legal fact that results in a specific person acquiring the right to manage a public infrastructure networks and devices of the corresponding type, at the same time causes the transfer of the easement in the public interest, created for the purposes of management of this infrastructure.
Keywords: javno dobro; stvarne služnosti; stvarno pravo